Implementasi Manajemen Berbasis Sekolah (MBS) Dalam Meningkatkan Prestasi Belajar Siswa Di SMP Negeri 13 Malang - Kholida, Siti; Alfatani, Ifan Ali (Universitas KH. A. Wahab Hasbullah, 2023)
In the context of regional autonomy, the implementation of School Based Management (SBM) is currently being developed, so that schools have the independence to be able to optimize all components/school members. Departing from this background, the author then wants to discuss it in his thesis and takes the title Implementation of School Based Management (MBS) in Improving Student Learning Achievement at SMP Negeri 13 Malang. The purpose of this research is to determine the implementation of School-Based Management (MBS), as well as supporting and inhibiting factors for the implementation of School-Based Management (MBS) in improving student learning achievement at SMP Negeri 13 Malang. This research use desciptive qualitative approach. The data collection techniques used were observation, interviews and documentation methods. The results of this research indicate that the Implementation of School-Based Management (MBS) in Improving Student Learning Achievement at SMP Negeri 13 Malang, which includes curriculum and teaching management, educational staff, school relations with the community, as well as special services has gone according to what was expected, namely able to improve student learning achievement. However, this does not mean that the Implementation of School Based Management (MBS) in Improving Student Learning Achievement at SMP Negeri 13 Malang is without obstacles.